SISTEM INFORMASI MANAJEMEN PLANING STOK DENGAN METODE MATERIAL REQUIREMENT - Muhamad Sidik; Hendri Rasminto (CV. ALIM'SPUBLISHING, 2023)
Technology currently plays an important role for a company. The implementation of information systems in companies is very popular because performance activities will run well, including the ease of data processing. In this case the company that wants information technology is PT. Arrgo Surya Abadi. The inventory system used at PT. Arrgo Surya Abadi still uses notes in the form of spreadsheets which are summarized every day, making it prone to errors in planning raw material needs, and it is difficult to control the use of production raw materials such as dyes. From this phenomenon, of course, a capable raw material planning information system is needed to process data and create raw material reports automatically. The aim of this research is to provide report data regarding the amount and time of raw materials procured to smooth production activities. The method used in this research is Material Requirement Planning (MRP). The results of this research conclude that with the existence of a computerized system at PT. Arrgo Surya Abadi can assist the production process related to procuring the right materials, in efficient quantities and time.